The Precarious Future of HIV and AIDS Programs in Zimbabwe Following International Funding Freeze: Impact and Strategic Interventions - Christopher Jimu (Journal of Epidemiology and Global Health)
Abstract Over the past few decades, significant progress has been made in the global fight against HIV and AIDS, largely driven by international funding mechanisms such as the President’s Emergency Plan for AIDS Relief (PEPFAR) and the Global Fund. These initiatives have been instrumental in expanding access to antiretroviral therapy (ART), implementing prevention programs, and strengthening healthcare infrastructure, particularly in Sub-Saharan Africa (SSA), a region disproportionately affected by HIV. Zimbabwe, in particular, has achieved remarkable success in combating the epidemic, recently meeting the UNAIDS 95–95-95 fast-track targets, a testament to sustained international support and national commitment. However, the recent suspension of foreign aid, including funding for HIV programs, threatens to undermine these gains. For Zimbabwe, a prolonged freeze could lead to a resurgence of new infections, an increase in AIDS-related mortality, and further strain on Zimbabwe’s already fragile healthcare system. This commentary examines the potential consequences of the aid suspension on Zimbabwe’s HIV and AIDS response and explores strategies to mitigate its impact.